Kienböck Disease: Quality, Accuracy, and Readability of Online Information. (July 2020) - Noback, Peter C.; Trofa, David P.; Dziesinski, Lucas K.; Trupia, Evan P.; Galle, Samuel; Rosenwasser, Melvin P.
Background: Patients with limited health literacy require online educational materials to be written below a sixth grade level for optimal understanding. We assessed the quality, accuracy, and readability of online materials for Kienböck disease (KD).Methods: "Kienbock's Disease" and "Lunate Avacular Necrosis" were entered into 3 search engines. The first 25 Web sites from each search were collected. Quality was assessed via a custom grading rubric, accuracy by 2 residents and a fellow, and readability by Flesch-Kincaid grade level (FKGL) and New Dale-Chall test. Web sites were stratified according to the search term, FKGL, order of appearance, and authorship type.Results: A total of 38 unique Web sites were included, of which 22 were assigned to "KD" and 16 to "Lunate Avascular Necrosis." The average quality score out of 30, accuracy score out of 12, and FKGL for all Web sites were 13.3 ± 7.3, 10.4 ± 1.9, and 10.5 ± 1.4, respectively. Web sites assigned to the term "Kienbock's Disease" had a significantly higher FKGL. Web sites of higher FKGL had significantly worse accuracy scores. Order of appearance had no influence. Physician specialty societies (PSS) had a significantly lower FKGL than Web sites of other authorship types.Conclusions: Despite concerted efforts by national organizations, the readability of online patient materials is above the recommended level for KD. Patients with limited health literacy will be most affected by this reality. Until readability improves, patients should continue to consult their physicians when uncertain and prioritize Web sites that are easier to read and produced by PSS.